Emotional Regimes Reflected in a Popular Ballad: Perspectives on Gender, Love and Protest in 'Scarborough Fair'. Issue 1 (2nd January 2016) - Garrido, Sandra; Davidson, Jane
Abstract : 'Emotional regimes' is a concept defined by William Reddy in 2001 and used in the history of emotions literature to refer to the modes of emotional expression and thought that are dominant in particular time periods and cultural contexts. Popular ballads provide a useful way of exploring emotions in their cultural contexts across different time periods because of their long life-span, and because of the way they are shaped and moulded by social beliefs during the processes of transmission. In this article we use the theoretical framework of emotional regimes to re-examine the popular English and Scottish ballad often known as 'Scarborough Fair' and three of its variants from three specific time periods: the Early Modern, the Victorian era and the twentieth century. We also report on a survey of 600 modern-day listeners who describe their response to the ballad. The discussion considers what the transformations to the song-text reveal about the changing viewpoints towards gender and love that were prevalent in the historical periods considered and in the twenty-first century.